SIMSArchive: Reflections on Processing 50 years of LIS Student Association Records - Hare, Maddie; Krause, Geoff (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2023)
A reflection on processing LIS student association records in preparation for their move to the Dalhousie Archives, from the perspective of an MI student. This reflection comments on the importance of preserving student knowledge, a workshop series that was developed to provide instruction and learning opportunities for archive-minded students, and key takeaways from the project that may be of interest or significance to other academic student associations grappling with managing and preserving the records of their organizations.